Design and indoor simulated experiment of pneumatic rice seed metering device - Guozhong, Zhang; Ying, Zang; Xiwen, Luo; Zaiman, Wang; Qiang, Zhang; Shasha, Zhang (International Journal of Agricultural and Biological Engineering, 2015)
In order to meet the agronomy demand for hybrid rice direct seeding, a novel precise pneumatic rice seed metering device was designed with groups of sucking holes plate, by which 3-4 seeds could be synchronously sucked and synchronously dropped into the paddy field. The plate was divided into five sections: seed sucking, seed clearing, seed carrying, seed dropping, and blank sections. The seeds were sucked in sucking section by the vacuum, carried and rotated to the dropping section with the plate, blown away in dropping section by the positive pressure air, and thrown into the dropping tube. The influences of the hole diameter, vacuum degree, and clear-up equipment on precision of metering device were discussed. Experiments were conducted to investigate the seeding precision and simulate the field emergence rates on the indoor seeding test-bed. The subjects were pregnant Indic hybrid Peizataifeng under two kinds of moisture content (23.43% and 26.07%). Other experiment conditions included the vacuum degree of 2.60 kPa, the rotation speed of seed sucking plate of 30 r/min, three sucking holes with a diameter of 1.6 mm, and the seed layer thickness of 25 mm. The seeding results showed that, in condition of no more than two seeds per hill, the emergence probabilities under the two moisture contents were 11.82% and 11.95%, respectively, and in condition of 3-4 seeds per hill, the results were 64.81% and 65.84%, respectively. With 2-5 seeds per hill, the results were 92.08% and 92.60%, respectively. If the emergence probability was 80%, under the two moisture contents, the no seed per hill probabilities were 1.33% and 0.80% respectively; the probabilities with 3-4 seeds per hill were 56.13% and 56.40% respectively; the probabilities with 5 or more seeds per hill were 10.67% and 10.13% respectively; the probabilities with 2-5 seeds per hill were 87.60% and 88.13% respectively. The results showed the simulated experiment was an efficient and economic method to assess the capability of pneumatic rice seed drilling metering device, and the precise pneumatic rice seed drilling metering device had a good prospect in practical application.Keywords: agricultural machinery, seeds, pneumatic seed metering device, precision hill-drop drilling, perpendicularity sucking plate, riceDOI: 10.3965/j.ijabe.20150804.1626Citation: Zhang G Z, Zang Y, Luo X W, Wang Z M, Zhang Q, Zhang S S. Design and indoor simulated experiment of pneumatic rice seed drilling metering device. Int J Agric & Biol Eng, 2015; 8(4): 10－18.